Student challenges and learning strategies at Hong Kong EMI universities - Pun, Jack (PLoS One, 2021)
The rapid trend towards globalization has led to the expansion of English as Medium of Instruction (EMI) in tertiary education. The academic challenges faced by non-native speakers have been broadly discussed in Anglophone countries, whilst those learning through EMI in the Chinese context are still underexplored. To examine Chinese EMI university students’ perceived language challenges in learning, as well as their language-related learning strategies, this study investigated 73 students studying at EMI universities in Hong Kong, taking account of their gender, EMI experience in higher education, and English exposure prior to tertiary education. Participants completed a survey to provide self-evaluations of their academic situation and their perceptions of their disciplinary learning. The study found that students perceived a relatively low level of language and learning challenges, and they showed a preference for using their second language (L2)-related learning strategies over strategies related to their first language. Specifically, male students tended to be more actively engaged in communication with their peers than females, and were more likely to search for additional learning support in English. In addition, first-year undergraduates perceived a greater degree of challenges in knowledge application and relied more on L2-related learning strategies than their senior counterparts. Although the importance of English exposure prior to higher education has been highlighted in many existing studies, this study found that prior exposure to English was neither connected with students’ perceived challenges nor their learning strategies.